2009
DOI: 10.1038/jhh.2009.45
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors for hypertensive disorders in pregnancy: a multivariate approach

Abstract: The study aimed to develop prediction algorithms for hypertensive disorders based on multivariate analysis of factors from the maternal history and compare the estimated performance of such algorithms in the prediction of early preeclampsia (PE), late-PE and gestational hypertension (GH) with that recommended by the National Institute for Clinical Excellence (NICE). Logistic regression analysis was used to determine which of the maternal characteristics and history had significant contribution in predicting ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
231
6
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(268 citation statements)
references
References 39 publications
19
231
6
12
Order By: Relevance
“…38 Similarly, the association between early-PE with high uterine artery PI and low serum PAPP-A is compatible with findings of extensive studies implicating impaired placental development and function in the pathogenesis of early-PE. [7][8][9] In the unaffected controls, the maternal serum concentration of IGFBP-3 decreased with fetal crown-rump length and was lower in women using ovulation induction drugs.…”
Section: Discussionsupporting
confidence: 81%
“…38 Similarly, the association between early-PE with high uterine artery PI and low serum PAPP-A is compatible with findings of extensive studies implicating impaired placental development and function in the pathogenesis of early-PE. [7][8][9] In the unaffected controls, the maternal serum concentration of IGFBP-3 decreased with fetal crown-rump length and was lower in women using ovulation induction drugs.…”
Section: Discussionsupporting
confidence: 81%
“…Nulliparity is widely reported as a risk factor for hypertensive disorders in pregnancy [13][14][15]. But in the present study, we found that multiparity was more associated with HDP as compared with nulliparity, however the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 55%
“…Ma már számos közlemény [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50] : 1,32). A császármetszés gyakorisága először szülőknél és többedszer szülőknél egyaránt lényegesen magasabb a 30 éves korosztályhoz képest.…”
Section: Növekvő Veszélyek Az Anya éLetkorának Előrehaladásávalunclassified